Energy justice for all? Rethinking Sustainable Development Goal 7 through struggles over traditional energy practices in Sierra Leone. (June 2017) - Munro, Paul; van der Horst, Greg; Healy, Stephen
Abstract: With Sustainable Development Goal 7, the United Nations has declared its ambition to ensure access to modern energy for all by 2030. Aside from broad appeals to differentiated responsibilities and 'greener' technologies, however, the goal leaves significant procedural questions unaddressed. This paper argues that the basic orientation of this approach is problematic, undermining possibilities for progress toward energy justice and equitable development. First, in framing the issue of global energy distribution in broad techno-managerial terms it obscures how particular geographies of energy poverty have been shaped by critical political economic influences. Second, in privileging modern forms of energy and focusing on an end state of universal adoption, over a broader goal of eliminating energy poverty, the approach of SDG7 presents tangible hazards to many of those it seeks to benefit. Using a case study of Sierra Leonean rural cooking energy policy, we demonstrate how the underlying mentality of SDG7 feeds into existing discourses that marginalise producers and users of 'traditional' energy sources, threatening important livelihoods. With such evidence, we argue that for justice in energy policy to be realised holistically, there is a need to question how our knowledge of energy 'problems' have emerged to avoid epistemologically autarchic policy positions. Highlights: Examination of the justice issues within the text of Sustainable Development Goal 7. Investigates how fuelwood is entangled with energy justice issues in Sierra Leone. Argues energy solutions need to shift away from simple technological fixes. Energy policy needs to be built on a range of energy knowledges and experiences.